ANALISIS KESIAPAN PEGAWAI MENERIMA PERUBAHAN UNTUK PENERAPAN BALANCE SCORECARD DI LINGKUNGAN PEMERINTAHAN (STUDI KASUS BPKAD KABUPATEN GIANYAR) - I Kadek Sumantra; Ni Ketut Murdani, S.Sos, SE, MM; i Putu Andini Desiyanti L., S.S., M.Hum (LPPM STIE Mujahidin, 2023)
This study aims to determine the readiness of BPKAD employees in the implementation of the Balance Scorecard seen through multidimensional readiness, secondly knowing the factors that affect the readiness of BPKAD employees to accept changes in the application of the Balance Scorecard, and knowing the difference in employee readiness to accept changes to the application of the Balance Scorecard in the work unit and the length of work at BPKAD. This research uses 2 (two) methods, namely qualitative and quantitative. Qualitative methods are used to identify and provide indepth knowledge on the problems of applying the Balance Scorecard. The qualitative method conducted in this study used primary data obtained through in-depth interviews with the Head of the Regional Financial and Asset Management Agency (BPKAD) of Gianyar regency and several employees from the implementation team of the Balance Scorecard implementation. quantitative methods are used to provide information on employee readiness for the implementation of the Balance Scorecard. The result of this study is that readiness to change is a multidimensional construct that is influenced by trust among employees by conducting descriptive analysis, the results show that BPKAD employees are only ready for the dimensions of Appropriateness and Personal Valence. The stages in the change process have not been fully carried out by BPKAD, so BPKAD needs to improve it. The above conditions affect the overall dimension of employee readiness for the implementation of the Balance Scorecard. Hypothesis testing that has been carried out there is no significant difference in employee readiness to change on the dimensions of appropriateness, management support, and change-specific efficacy between work units and on the length of work. This means that employees' perceptions of these dimensions are not influenced by factors such as work units and length of work